Textiles for sportswear - Shishoo, Roshan (Woodhead Publishing, 2015)
Textiles for Sportswear is an important book that systematically covers key trends in design and materials, the use of novel and smart fabrics, and a range of specific applications. The book begins by surveying the principles of textile applications in sport, including design, materials, and production technology. The uses of smart textiles in sportswear are then examined, from intelligent materials to wearable technology. Final sections of the text explore comfort in sportswear, sportswear for protection, and recent advances in sportswear technology that are currently being applied to par.
Keywords: Sport clothes.; Sporting goods -- Materials -- Research.; Textile fabrics -- Technological innovations.; elektronické knihy; electronic books